Pemanfaatan Media Sosial dalam Pemasaran Produk UMKM (Ikan Keruk) di Kelurahan Air Jukung, Kabupaten Bangka - Suprayuandi Pratama; Ariska Ariska; Melly Melly; Helmalia Helmalia; Dina Mariska; Ullia Asyhari; Lupita Lupita; Tsabita Putri Anjani; Candra Alamsyah; Junaidi Junaidi (Jurnal Pengabdian Masyarakat Waradin, 2024)
Technological developments have brought many changes, especially in the way we interact and do business. Currently, social media is widely used as a marketing platform for MSME products, this is because through social media the dissemination of information occurs quickly and it also allows MSME players to communicate with consumers directly and promote their products at relatively low costs. However, there are still many MSME actors who have not optimally utilized social media, such as dredged fish MSME actors in Air Jukung sub-district who only use Facebook to market their products. Because of this, the aim of this service is to provide assistance and direct practice in using social media to MSMEs in dredging fish in Air Jukung sub-district in optimizing marketing strategies in an interesting and unique way. The method for this service is in the form of training in making unique posters through the Canva application and interesting content on social media and processing it to attract consumer interest. The results of the service activities ran smoothly and received a positive response from social media users.